THE EFFECT OF USING HERRINGBONE TECHNIQUE ON STUDENTS’ READING COMPREHENSION AT THE THIRD SEMESTER STUDENTS OF ENGLISH DEPARTMENT AT UNISI TEMBILAHAN - Maizarah Maizarah; Sri Erma Purwanti (Universitas Sarjanawiyata Tamansiswa, 2020)
The present study aims to find out the effect of using Herringbone technique on students’ reading comprehension at the third semester of English Department in Unisi Tembilahan. This study is an experimental research. The data were collected by using test. The results indicate that the pre-test average is 31,06 and in post-test is 41,18. The obtained t-observed is 4,6, whereas the t-table is 2,12 in 5%. The t-observed score is higher than he t-table (4,6>2,12). It means that ha is accepted while ho is rejected. Since t-observed score is higher than the t-table, Herringbone technique is effective on students’ reading comprehension at the third semester students of English Department in Unisi Tembilahan. Based on the finding, the researchers assume that Herringbone technique can be used as one of the alternative techniques in the teaching reading comprehension.